2010
DOI: 10.1186/1476-511x-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid measures for prediction of incident cardiovascular disease in diabetic and non-diabetic adults: results of the 8.6 years follow-up of a population based cohort study

Abstract: BackgroundDiabetes is a strong risk factor for cardiovascular disease (CVD).The relative role of various lipid measures in determining CVD risk in diabetic patients is still a subject of debate. We aimed to compare performance of different lipid measures as predictors of CVD using discrimination and fitting characteristics in individuals with and without diabetes mellitus from a Middle East Caucasian population.MethodsThe study population consisted of 1021 diabetic (men = 413, women = 608) and 5310 non-diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…In the United Kingdom Prospective Diabetes Study, LDL-C was the strongest predictor for CVD, and hypertriglyceridemia was not a predictor [37]. In contrast, in other case-control studies, the results were conflicting [9,38,39]. In one study, hypertriglyceridemia was an independent risk factor for CVD only in the high non-HDL-C group [12].…”
Section: Triglyceride and Cardiovascular Disease In Diabetic Patientsmentioning
confidence: 91%
“…In the United Kingdom Prospective Diabetes Study, LDL-C was the strongest predictor for CVD, and hypertriglyceridemia was not a predictor [37]. In contrast, in other case-control studies, the results were conflicting [9,38,39]. In one study, hypertriglyceridemia was an independent risk factor for CVD only in the high non-HDL-C group [12].…”
Section: Triglyceride and Cardiovascular Disease In Diabetic Patientsmentioning
confidence: 91%
“…5 Recently we showed that dyslipidemia is commonly associated with diabetes and CVD events among Iranian populations. 6,7 Dyslipidemia could lead to hypertension by mechanisms such as endothelial dysfunction resulting in impaired nitric oxide production, release and activity, and structural changes in large arteries following atherosclerosis. 8,9 Additionally, hypertension and dyslipidemia, as the components of metabolic syndrome may have universal mechanistic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Third, HDL-cholesterol was a specific determinant for Okinawa men and women, but not for Nagano men and women. diovascular diseases 24,25) . In the current study, LDLcholesterol and non-HDL-cholesterol were determinants in Okinawa and Nagano men.…”
Section: Discussionmentioning
confidence: 99%